(3JMaI GdWGdH HTQM ebUhQI GdefGbH (B((3efGbH GdUMGHI hQLGd GdWQjbI GdCMeOjI(B)s - (3CHh GdYHGS CMeO Hf YHO GdhgGH GdhRjQ GdZSGfj,J (B1146 (3g` s
(3ChdgG (B:s
(3CeG HYO , aEfi cfJ bHd gPG GdChGf hGdCehQ aj EfJXGe , HhLhO Pi GdLdGd hGdEYXGe CHj GdYHGS SjOj CMeO Hf YHOGddg OYJfj eTGgOI WdYJg Gf bdJ ebUhQI s
(3BNQgG (B:s
(3GfJgi GdSaQ GdChd ef JMaI GdWdH HTQM ebUhQI GdefGbH GdJj ETJedJ Ydi SfO SjOfG CMeO Hf YHOGddg heBKQg hefGbHg hcQGeGJg , QVi Gddg Yfg faYfG Hg Bejf s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B97 s
Keywords: (3GdJGQjNs